Vertrauen, Solidarität und Emotionen in Non-Profit-Organisationen. Eine soziologische Analyse des Dritten Sektors in Deutschland - Weggen, Jenny (Hamburg University Press, 2017)
This qualitative study explores the significance and interrelation among trust, solidarity and emotions in third-sector organisations in Germany. Non-profit organisations (NPOs) are identified as highly emotional. Social interactions within these organisations are shaped by the control mechanism of trust and the guiding principle of solidarity. NPOs rely on interaction among the three social phenomena of trust, solidarity and emotions, which are essential for cooperation and therefore for an organisation to function. This research addresses both the theoretical background and everyday practice of trust, solidarity and emotions and shows the conditions under which they grow and function as well as their interdependencies within NPOs.